FACTORS OF TOURIST PERCEIVED VALUE OF INDONESIA SHOPPING TOURISM - Filda Rahmiati; Grace Amin (FIRM Journal of Management Studies, 2019)
Shopping becomes a relevant component. Shopping has become a factor that influences the choice of destination, travel, travel and travel. With the desire to develop, it is an interesting phenomenon for policy makers, academics and business leaders around the world. The city of Bandung, as one of the cities called "shopping paradise" has attracted many foreign tourists (tourists). The purpose of this study is to analyze the factors of foreign tourists perceived value towards shopping tourism in the city of Bandung. The results of the analysis in this study stated that there are 5 (five) new factors of tourist perceived value of shopping tourism. The five factors are: (1) Emotional Value, (2) Value for Money, (3) Social Value, (4) Hedonic Value, and (5) Functional Value. The most dominant factor is Emotional Value because it has the highest Eigen Value. This research recommend coordination between the Government of Bandung City to improve the city infrastructure so as to provide comfort for foreign tourists when visiting the city of Bandung. In addition, there are also innovations in terms of payment when shopping, innovations in shopping centers that are expected to increase tourist satisfaction so the creation of repeat visits also recommends to other foreign tourists.